Baboon biogeography, divergence, and evolution: Morphological and paleoecological perspectives. Issue 145 (August 2020) - Elton, Sarah; Dunn, Jason
Abstract: Papio originated in the early Pleistocene and diverged into multiple species, six of which are extant. Among parapatric Papio species, there are obvious phenotypic differences that arose during the radiation of the genus. We use data from modern baboon ecology and morphology, as well as fossils and paleoecology, to examine baboon biogeography, divergence, and evolution, focusing on skull form and body mass. To provide context, techniques of historical biogeography, combining data from modern distributions in statistical models alongside qualitative assessments of the fossil record, were used to estimate ancestral ranges in papionins. The ancestral range of Papio was estimated to be in South Tropical Africa rather than in the far south of the continent, followed by multiple movements south and west. Progress to the north and east may have been slowed because of high-density blocking of niches by other monkeys. Geometric morphometric data were used in partial least squares analysis with dietary, environmental, and other variables to investigate skull differentiation. Environment was significantly correlated with skull form, but diet emerged as more significant. Exploitation of subterranean foods was found to be an important influence on skull morphology. Bayesian modeling of cercopithecid body mass data allowed reconstruction of ancestral body mass and showed a pattern of accelerating body mass evolution in a number of lineages. This appears to be related to exploitation of terrestrial niches in the Pliocene, with terrestriality also implicated in the large geographic distributions of many fossil and modern papionins, including Papio . Given the greater heterogeneity of body masses in males, size differentiation within Papio seems most likely to be linked to sexual selection rather than environmental factors, although further work is required to examine the relative importance of plasticity versus local adaptation in shaping baboon phenotypic variation.